Modelling levels of nitrous oxide exposure for healthcare professionals during EMONO usage. Issue 1 (December 2016) - Pichelin, Marine; Billoet, Catherine; Caillibotte, Georges
Abstract Background Computational fluid dynamics (CFD) has been used to compute nitrous oxide (N2 O) levels within a room during the administration of an equimolar mix of N2 O/oxygen (EMONO) in the clinical setting. This study modelled realistic scenarios of EMONO usage in hospital or primary care, in order to estimate the potential N2 O exposure of healthcare professionals (HCP) with routine EMONO use and to provide guidance for EMONO users. Methods Sixteen scenarios were defined by carrying out a survey of practitioners. CFD simulations were performed for each scenario and N2 O concentrations over time were calculated. N2 O exposures (time-weighted average of concentration over 8 h [TWA-8 h]) were calculated at the HCPs' mouth to be compared with a predefined occupational exposure limit (OEL). Results Administration duration and ventilation type were the main factors influencing N2 O levels; ventilation type also influenced wash-out time between EMONO administrations. N2 O concentration showed a plume distribution towards the ceiling and was highly heterogeneous, highlighting the importance of measurement location. Although estimated TWA-8 h varied widely, 13 of the 16 scenarios had an N2 O TWA-8 h of <100 parts per million. Conclusions Data demonstrate that EMONO usage in well ventilated rooms – as recommended – helps to ensure that N2 O exposure does not exceed the OEL and does not signal any major risks for HCPs when recommendations are followed. Although these data are numerical simulations and should be considered as such, they can provide guidance for EMONO users.